PENGGUNAAN MEDIA POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Dahniar (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Technological developments affect various sectors in Indonesia, including the most facilitated is technology in the field of education which also requires teachers to master technology so they can compete with world progress. In essence, technology includes learning media that makes it easier for students to understand learning material. And the good news is that learning media can be combined with conventional methods where the boredom caused can be minimized because the media offers meaningful and varied learning so that it can attract students' attention to learning. Among the various kinds of existing learning media, the right learning media for this problem is PowerPoint media. One of the advantages of PowerPoint learning media is to help students concentrate in the learning process so as to generate enthusiasm for learning and increase learning motivation. This is due to the interaction that occurs directly between students and learning resources. A good learning process will result in an increase in student learning outcomes.